IMPLEMENTASI KURIKULUM BERBASIS BUDAYA MELAYU RIAU DI SD NEGERI 189 PEKANBARU - Adhinda Chaerani; Ruth Febriana, Tiffany Valeria Br Tarigan, M. Jaya Adi Putra, Mauliatun Nisa (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze the implementation of the culture-based curriculum of Malay Riau at SD Negeri 189 Pekanbaru. This curriculum is expected to introduce local wisdom and shape students' character to love their regional culture. Although it has been integrated into the learning activities, the implementation of this culture-based curriculum still faces various challenges. One of the main challenges is the lack of deep understanding among teachers regarding Malay Riau culture, as well as students' perceptions that local culture is irrelevant to their current lives. This study uses interviews and observations to gather data from teachers. The results indicate that although this curriculum positively impacts students' cultural understanding, its implementation still requires improvement in terms of resource support and community involvement. It is hoped that with continuous evaluation and improvement, the culture-based curriculum of Malay Riau can be more effectively applied to preserve local culture and develop better character among students.